(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The scientific, theoretical, methodological and practical foundations of the knowledge process, i.e. the theory of education, imparting knowledge, and teaching are dealt with by an independent department of pedagogy, didactics - educational theory. Didactics is a Greek word. ’lib, "didasko", means to teach, teach. In the process of studying and analyzing the laws of education, knowledge about the concept of education, its essence, content and tasks, principles and forms of education is explained. Didactics seeks answers to questions of pedagogy such as "what to teach", "what to teach" and "how to teach".